Pengaruh Modal Kerja Usaha dan Kualitas Produk Bakso Terhadap Pendapatan UMKM - Ayu Wandira; Vidya Fathimah (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
The purpose of this research is none other than to find out the income level of Takasimurah fried meatball MSMEs in 2020-2022 by paying attention to business working capital and product quality. The benefit of this research is that both the community and MSME actors can consider the efforts to formulate a plan in determining decisions on working capital and product quality related to the achievement of income that MSMEs want to obtain. Research location on Jalan. Primary Source Medan Amplas District. The object of research is the financial reports and UMKM customers of Taksimurah fried meatballs. This research approach is descriptive quantitative. Descriptive quantitative research is a research method that shows the results of a collection of quantitative or statistical data such as an as-is survey. The test results obtained Tcount working capital 3.879 > Ttable 2.011 and Tcount product quality -0.337 <Ttable 2.011 thus for the partial only the working capital variable had a positive effect on the income variable, while the product quality variable had no effect on income. Then test F, Fcount is 6.533> from Ftable 4.79. shows that the variables (X1) and (X2) simultaneously (simultaneously) have a positive effect on income in MSMEs. Continuing the multiple linear test results of the variables x1 and x2 affect/give an impact of 46.4%.